Data and Process in Information Centered Creative Practice - Judy Malloy (MatLit)
With increasing availability of online data and data visualization software, information art — and its historic role in environmental and social change activism — is increasingly relevant in contemporary creative practice. Beginning with a summary of early conceptual and Fluxus information-based art, this review paper explores uses of information by artists and by writers of electronic literature in the following areas: the role of documentation in the origins of Information art; the role of process in the evolution of information art; the role of research and archives; and the role of data in shaping visual objects and texts. The paper concludes with pointing out issues in using commercial databases as sources of information for black identity, for Native American communities, and for feminist research. The conclusion also points out the importance of research design, ethical considerations in the use of data, and the importance of seeking opportunities for collecting and analyzing data that transcend usual sources.